The history of medical or health policing from the antiquity to the end of the 19th century (Academic Journal of Internal Affairs, 2020)
Among nowadays’ daily news appeared like a bombshell the flu-like disease caused by the coronavirus and immediately began to dominate world news. According to the shots presented obtained outstanding attention the healthcare regulations, the quarantine, the protective means and the closure of the Chinese city Wuhan, where coronavirus appeared in masses and took several hundred victims in January 2020. The coronavirus is new, but the developed health crisis and its handling is not new in the history of policing. This paper presents the short history of medical or health policing from the antiquity to the end of the 19th century.
Keywords: policing; healthcare; medicine; epidemic control